Penerapan Metode Make A Match Untuk Meningkatkan Hasil Belajar Materi Pendidikan Agama Islam - Eva setianingsih; Nada ulfah; Titin sumarni; Zul syahrin; Putra, Purniadi (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The make a match learning method is a learning method that invites students to learn actively and aims to ensure that students have a spirit of independence in learning and foster creativity so that they are able to make innovations. This make a match method has a cognitive level, from the level of knowledge, understanding, application, analysis and creativity. The aim of this research is to determine the increase in learning outcomes by applying the make a match method of Faith in the Messenger of Allah material for class V students at SDS IT Sulthoniyah Sambas. The data sources in this research are student and teacher respondents as well as informants, namely the Principal and documents. This research technique consists of observation, tests and interviews. The conclusion from this research is that during the learning process, the teacher delivered the material and the application of the method was good. Teachers provide motivation to students to be enthusiastic about learning. By implementing the make a match method in class V, it can increase student learning activities. Furthermore, based on the results of the evaluation of classical completeness learning, the students' scores reached an average of 78.5 with a percentage of 90% complete.